Perpaduan Determinan Individu dan Tingkat Ekologi terhadap Kejadian Infeksi Malaria di Endemis Malaria (Media Kesehatan Masyarakat Indonesia, 2019)
Epidemiological studies of malaria regarding risk factors are limited to knowing the biobehavioral effectat the individual level. Determinant analysis at various levels with various methodological problems has notbeen widely considered by epidemiologists to date. This study used hybrid design ecological studies. Qualitativestudies were conducted to look at the parameters of village conditions in response to operational policies onmalaria prevention programs. The analysis carried out was multilevel logistic regression and content analysis.Samples were taken in stages from 1,206 residents in 240 households in 30 villages in 3 malaria endemic districtsof South Lampung Regency & Pesawaran. The incidence of malaria infection was found [with parasitic indicators(+)] in 30 malaria endemic sub-villages in South Lampung Regency & Pesawaran District of 11.2%, with themajority of malaria plasmodium species being 55.8% P. Vivax, followed by P. Falciparum (41.5%), and the lowestwas P. Malariae (2.7%). The role of the individual level (level 1) is 0.17%, the role of the household level (level2) is 43.8% and the role of the village level (level 3) is 55.9% in explaining the incidence of malaria infection.Conclusions from the results of the study found that the difference in incidence of malaria infection in individualsis more determined by contextual factors (level of household (level 2) and village level (level 3) compared tocompositional factors (individual level (level 1).
Keywords: Infeksi malaria; multilevel; kontekstual; komposional